REGOLITH HISTORY OF THE AUBRITIC METEORITE PARENT BODY REVEALED BY NEUTRON CAPTURE EFFECTS ON SM AND GD ISOTOPES - Hidaka H.; Yoneda S.; Marti K. (My University, 2006)
Enstatite achondrites (aubrites) when compared to other stone meteorites have unusually long cosmic-ray exposure (CRE) ages. We report here the 150Sm/149Sm and 158Gd/157Gd ratios in six different structural phases, i.e., light and dark (shocked) grains and in matrix materials of Pesyanoe, in three different fragments from Pena Blanca Spring, and in one from Norton County, Shallowater, and Khor Temiki, to investigate the regolith history on the aubrite parent body. The results from phases components of Pesyanoe confirm earlier reported evidence for regolith irradiation of several aubrites. The inferred neutron fluences for six Pesyanoe separates vary between (2.13 and 2.82) ? 1016 n cm-2. The fluences also significantly exceed those expected from cosmic-ray irradiation during transit to Earth and approach those observed in the lunar regolith. These observations confirm that the brecciated Pesyanoe meteorite, which contains solar wind (SW) gases only in dark phases, was processed in a regolith and that structural phases were differentially irradiated before compaction. On the other hand, in some aubrites (Mt. Egerton, Shallowater, Pena Blanca Spring, Norton County) neutron capture effects may entirely be due to space irradiation.
Keywords: ACHONDRITE; GADOLINIUM; ISOTOPIC RATIO; REGOLITH; SAMARIUM; SOLAR WIND; KANSAS; NORTH AMERICA; NORTON COUNTY; UNITED STATES